Perbedaan Strategi Coping Mahasiswa Akhir Dalam Menghadapi Stres Akademik Ditinjau Dari Jenis Kelamin - Dalimunthe, Syaiful Izhar; Daulay, Annisa Arrumaisyah (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
The demands that occur to students in the final semester are very diverse, demands that can cause students to often experience academic stress such as final assignments in the form of theses or scientific journals that cause unpleasant situations, if this situation is left unchecked it can cause stress in students. The way students reduce stress due to academic demands is called a coping strategy. Coping strategies in students based on gender by involving students and female students. This study aims to determine the differences in coping strategies based on the forms of problem focused coping and emotional focused coping between students and female students in the department of guidance and islamic counseling, faculty of da'wah and communication of UIN North Sumatra. The subjects in this study amounted to 50 people consisting of 25 students and 25 female students. Sampling of subjects in this study using purposive sampling using instruments in the form of questionnaires with problem focused coping and emotional focused coping scales. Data analysis used is comparative analysis using the t test. based on the results of the study showed the results of the hypothesis t = 1.543 with p≥ 0.05, and in EFC showed the results of the hypothesis test t = 0.422 with p≥ 0.05. This means that there are differences in coping strategies in the form of PFC and EFC in students with male gender and with female gender. Students with male gender have coping strategies in the form of PFC that are higher than women while with female gender have coping strategies with higher forms of EFC.